Juridical Analysis of the National Inquiry of the Nation Human Rights Commision in Guaranteeing the Constitutional Existence of the Rights of Customary Law Communities to Customary Forest Areas - M. Yusup Febrian (JURNAL HUKUM SEHASEN, 2023)
The National Inquiry on the Juridical Analysis of the National Commission on Human Rights (Komnas HAM) aims to ensure the constitutional existence of the rights of customary law communities over customary forest areas. The inquiry focuses on the rights of customary law communities over their territories in forest areas. The first book of the inquiry report, entitled "National Inquiry Report of the National Commission on Human Rights on the Rights of Customary Law Communities in Forest Areas," contains the national inquiry as well as the findings and recommendations. The report highlights that customary law communities have a recognized and protected position under Indonesian national law. However, they often experience arbitrary takeover of customary forests, takeover of customary forests without notification of the purpose and implications of their use, and discriminatory behavior by police, military, and government officials towards customary law communities. Therefore, legal protection for customary law communities over customary forests is necessary to ensure their constitutional rights.